Macrophage‐targeted delivery of siRNA to silence Mecp2 gene expression attenuates pulmonary fibrosis. Issue 2 (18th January 2022) - Mou, Yong; Wu, Guo‐Rao; Wang, Qi; Pan, Ting; Zhang, Lei; Xu, Yongjian; Xiong, Weining; Zhou, Qing; Wang, Yi
Abstract: Idiopathic pulmonary fibrosis (IPF) is a progressive interstitial lung disease characterized by the infiltration of macrophages in the fibrotic region. Currently, no therapeutic strategies effectively control disease progression, and the 5‐year mortality of patients after diagnosis is unacceptably high. Thus, developing an effective and safe treatment for IPF is urgently needed. The present study illustrated that methyl‐CpG‐binding protein 2 (MECP2), a protein responsible for the interpretation of DNA methylome‐encoded information, was abnormally expressed in lung and bronchoalveolar lavage fluid samples of IPF patients and mice with onset of pulmonary fibrosis. And further studies verified that the overexpression of MECP2 occurred mainly in macrophages. Inhibition of Mecp2 expression in macrophages robustly abrogated alternatively activated macrophage (M2) polarization by regulating interferon regulatory factor 4 expression. Accordingly, cationic liposomes loading Mecp2 small interfering RNA (siRNA) were raised for the treatment of pulmonary fibrosis. It was noted that the liposomes accumulated in the fibrotic region after intratracheal injection, especially in macrophages. In addition, intratracheal administration of Mecp2 siRNA‐loaded liposomes significantly reversed the established pulmonary fibrosis with few side‐effects and high safety coefficients. Collectively, these results are essential not only for further understanding the DNA methylation in pathogenesis of IPF but also for providing a potent therapeutic strategy for IPF treatment in the clinic practice.